PEMBERDAYAAN KADER SARISEJAYA DALAM PEMBUATAN PENCIL BOX BAMBOO DENGAN MOTIF BATIK DURIAN SEBAGAI UPAYA MELESTARIKAN BUDAYA LOKAL LUBUKLINGGAU - Supriyanto Supriyanto; Isbandiyah Isbandiyah (LP4MK STKIP PGRI Lubuklinggau, 2023)
This activity aims to ensure that Sarisejaya cadres acquire (1) a comprehensive understanding of Lubuklinggau's local culture preservation efforts and potential, and (2) proficiency in crafting bamboo pencil boxes adorned with durian batik motifs. Employing socialization and demonstration methods, the outreach activities imparted diverse insights on Lubuklinggau City's cultural tourism potential and local culture preservation. Subsequently, partners engaged in hands-on demonstration activities, crafting bamboo pencil boxes featuring durian batik motifs. Results revealed a commendable 76% understanding level and an impressive overall participant score of 78.6. Sarisjaya cadres demonstrated highly proficient skills, achieving an average score of 85.02, categorizing them in the